The Winter's Tale Shakespeare Children's Story - Shakspeare, William (USA Sweet Cherry Publishing, 2013)
Shakespeare$1 (Bs Timon of Athens is the tale of a rich Athenian who lived a lavish life, spending his wealth on his friends. Eventually, when his wealth ceases and he asks his friends for help, Timon is shocked to find that none of them are prepared to do so. This fills him with hatred for humanity, and he goes on to live the life of a hermit. About Sweet Cherry Easy Sweet Cherry Easy Classics adapts classic literature into illustrated stories for children, introducing these timeless tales to a new generation.s
shelving location L
Keywords: english